Pharmacoinformation analysis of the molecules of the drug Klimaktoplan - I. Yu. Torshin; O. A. Gromova; N. I. Tapilskaya (Фармакокинетика и Фармакодинамика)
An analysis of an array of publications on naturaL extracts of tsimitsifuga, sepia, sanguinaria included in the preparation KLimaktoplan, showed that only the extracts of tsimitsifugi have more than 800 studies. The main active principles of the Klimaktoplan are synergistically interacting triterpene gLycosides, cymic acid derivatives of cymicifuge and naturaL pigments - brown melanin (sepia) and red sanguinarine (extract of Canadian sanguinaria). The results of fundamental and clinical studies of molecules of natural extracts in the KlimaktopLan indicate the following pharmacologicaL effects: anti-inflammatory, antidiabetic, vasodilator, hepatoprotective, spasmolytic, antiatherosclerotic, antitumor. Combination of components in the Klimaktoplan causes the effectiveness of the drug not onLy for the treatment of hot flashes, but a comorbid pathoLogy characteristic of the postmenopausal period. The possibility of combining extracts of Cimicifuga with other natural extracts (sepia, Canadian sanguinaria, etc.) is considered.